Impact of omega-3 fatty acids supplementation on the gene expression of peroxisome proliferator activated receptors-γ, α and fibroblast growth factor-21 serum levels in patients with various presentation of metabolic conditions: a GRADE assessed systematic review and dose–response meta-analysis of clinical trials - Ahmadi, Amirhossein Ramezani; Shirani, Fatemeh; Abiri, Behnazi; Siavash, Mansoor; Haghighi, Sasan; Akbari, Mojtaba (Frontiers in Nutrition, 2023)
There is some debate about the effects of omega-3 fatty acids on the regulation of adipose tissue related genes. This systematic review and meta-analysis aimed to evaluate the effects of omega-3 fatty acids supplementation on the gene expression of peroxisome proliferator activated receptors (PPAR-α and PPAR-γ) and serum fibroblast growth factor-21 (FGF-21) levels in adults with different presentation of metabolic conditions. To identify eligible studies, a systematic search was conducted in the Cochrane Library of clinical trials, Medline, Scopus, ISI Web of Science, and Google Scholar up to April 2022. Eligibility criteria included a clinical trial design, omega-3 fatty acids supplementation in adults, and reporting of at least one of the study outcomes. Effect sizes were synthesized using either fixed or random methods based on the level of heterogeneity.Fifteen studies met the inclusion criteria. Omega-3 fatty acids supplementation significantly increased the PPAR-γ (10 studies) and PPAR-α (2 studies) gene expression compared to the control group (WMD: 0.24; 95% CI: 0.12, 0.35; P<0.001 and 0.09; 95% CI: 0.04, 0.13; P<0.001, respectively). Serum FGF-21 (8 studies) levels exhibited no significant change following omega-3 fatty acids supplementation (P=0.542). However, a dose-response relationship emerged between the dose of omega-3 fatty acids and both PPAR-γ gene expression and serum FGF-21 levels. Overall, this study suggests that omega-3 fatty acids supplementation may have positive effects on the regulation of adipose tissue related genes in patients with various presentation of metabolic condition. Further research is needed to validate these findings and ascertain the effectiveness of this supplementation approach in this population.